KARAKTERISTIK MORFOLOGI DAN KLASIFIKASI TANAH INCEPTISOL PADA BEBERAPA SISTEM LAHAN DI KABUPATEN JENEPONTO SULAWESI SELATAN - Ulfiyah A. Rajamuddin; Idham Sanusi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
This study aims to determine the morphological characteristics and classification of Inceptisol on several different land systems in Jeneponto . Sampling was carried out at 4 profiles in Tamalatea, Bangkala and West Bangkala Regency. This study as a descriptive exploratory study by ground surveys in the field and is supported by data from laboratory analysis. Results of soil morphological showed are solum shallow, dominated by clay texture, color range varies from yellowish gray to dark brown, angular blocky structure with average development level, hard consistency when dry. Land classified into sub order usteps with a great group haplustepts, there are four sub-groups namely udertic haplustepts, oxic haplustepts, lithic haplustepts and vertic haplustepts. Key Words : Inceptisol, morphological characteristics, soil classification